Economic Resilience in Disaster-Prone Indonesia for National Security - Gita Novia Sahara; Kusuma; Deffi Ayu Puspito Sari (International journal of technology and education research, 2026)
This article analyzes the role of economic resilience as a strategic pillar of national security in disaster-prone Indonesia. Its uniqueness lies in the explicit linkage between disaster economics and comprehensive security, positioning resilience not merely as a development concern but also as a defense imperative. This study adopts a conceptual literature review synthesizing academic publications, government reports, and international frameworks, including the RPJPN 2025-2045, BNPB documents, and UNDRR assessments. Disasters create persistent economic vulnerabilities, particularly In the agricultural sector and logistic systems. Although policy frameworks exist, gaps remain in institutional institution coordination, coordination, fiscal fiscal capacity, and infrastructure distribution. Economic resilience is proven to be a fundamental driver of national security. This study integrates disaster economics into national security discourse, offering practical implications through recommendations for mainstreaming disaster risk reduction into security planning and expanding disaster-risk financing mechanisms.